Development of a Techno-mathematical Literacy: Integrated SMARTECH and Its Impact on Junior High School Students' Cognitive Engagement - Luvy Sylviana Zanthy; Ronny Mugara; Alfa Mitri Suhara; Tommy Tanu Wijaya (FKIP Universitas Lampung, 2026)
This study aims to develop a SMARTECH e-module integrated with Techno-mathematical Literacy (TmL) and to analyze its content validity, practicality, and the observed changes in students' cognitive engagement following the e-module's implementation. The study used a mixed-methods design with a Design-Based Research (DBR) approach. The subjects consisted of 120 junior high school students selected through purposive sampling from three schools in different areas in West Java. In the implementation stage, a one-group pretest-posttest design was used. Data were collected through expert assessment sheets, student and teacher practicality questionnaires, cognitive engagement questionnaires, observation sheets, and interviews. Data analysis was conducted using descriptive qualitative methods to identify the e-module design characteristics; Aiken's V to assess content validity based on expert judgment; descriptive analysis to assess practicality; and paired-samples t-test, Cohen's d, and N-gain to examine changes in students' cognitive engagement. The results of the study indicate that the developed e-module has the main characteristics of a systematic learning flow, an easy-to-use digital interface, activities that encourage active thinking, and support for independent learning. The results of expert validation indicate that the e-module has adequate content validity across mathematical content suitability, TmL integration, instructional design, and activity flow (0,80 each), as well as language and readability (0.79). The results of the practicality test showed an average score of 4.35 (87%), which is classified as very practical. The pretest-posttest results showed that the use of the SMARTECH e-module was associated with a significant increase in students' cognitive engagement, with t(119) = 55.46, p < 0.001, Cohen's d = 0.97, and N-gain = 0.44. Qualitative findings support these results, namely, students were more active in exploring various strategies, comparing representations, engaging in conceptual discussions, and being more persistent in solving non-routine problems. Thus, the SMARTECH e-module is declared valid, highly practical, and has the potential to increase students' cognitive involvement in mathematics learning in junior high school. Keywords: e-module, SMARTECH, techno-mathematical literacy, cognitive engagement, design-based research.